EXPLORING HABITAT APPROPRIATION IN THE TRADITIONAL FABRIC OF AIT ATTELI VILLAGE, KABYLIE (ALGERIA) - Sadjia Halit,; Abderzek Iddir,; Saif Eddine Chettah,; Abdelkader Laafer, (International Journal of Innovative Technologies in Social Science, 2024)
This article examines the appropriation of housing forms within the village fabric of the Kabylian region in northern Algeria. The region has experienced significant architectural, spatial, and socio-cultural transformations, affecting both existing structures and newly produced forms. The study focuses primarily on spatial and architectural elements, utilizing observations, visits, and surveys of various cases. This is complemented by a socio-cultural analysis based on interviews and survey guides to identify existing housing typologies and the villagers' aspirations, as well as the broader social context. Several types of housing were identified, including villas, blocks of flats, and apartments. Residents appropriate these different types by integrating modern elements while retaining traditional aspects. This duality is evident in both architectural features and socio-cultural practices. The mechanisms of appropriation reveal an ambivalence in how villagers occupy their dwellings: while there is a strong desire for modernity to meet needs for comfort, security, and privacy, there remains a deep attachment to traditional structures and the values, practices, and traditions of Kabylian village society.